Faktor yang Berhubungan dengan Resiko Kematian Neonatal di RSIA Pertiwi Makassar - Sunarti; Padhila , Nur Ilah (An Idea Health Journal, 2023)
The neonatal period is the period most at risk for survival. Neonatal deaths occupy the highest proportion that occur in newborns in the world. This is caused by several factors including mother's age, mother's education, parity, LBW, ANC services. The aim is to determine the risk factors associated with neonatal death at RSIA Pertiwi Makassar. The research design is an analytic survey research using a cross-sectional study approach with a statistical chi-square test with a significant ? = 0.05. Total of 57 respondents with purposive sampling technique. Data collection uses an observation sheet. Data processing using a computer program presented in the form of tables and narratives. The results of this study indicate that there is a relationship between maternal age and neonatal death with a p value = 0.021 > ?=0.05, there is a relationship between maternal education and neonatal death with a p value = 0.001 <?= 0.05 and there is a relationship between parity factors with neonatal death with p value = 0.000 <?=0.05, The conclusion of this study shows that there is a relationship between age, education and maternal parity with the risk of neonatal death. It is recommended for health workers to provide counseling to pregnant women and expectant mothers which is focused on low maternal education and the need to improve family planning methods (KB) so that the number of parities can be reduced.